Chemical composition of essential oil extracted from flowers of Hypericum PerforatumL.plant from two different regions of Tartous – Syria - مسلم, هديل; حويجة, عماد; حماد, ياسر; معلا, نزار (Latakia University Journal -Basic Sciences Series, 2023)
Flowers of Hypericum PerforatumL.plant (Hypericum SP genus , Hypericaceae family), was collected from two different regions of Tartous: Qadmus region (900m), Einaza region (450m),and the essential oil was extracted by Hydrodistillation using the Cleveger apparatus ,where the weight percentage of extracted essential oil stood at: (0.39%), (0.26%) forQadmus, Einaza region respectively. The Chemical composition of essential oil obtained from flowers of Hypericum Perforatum L. was analyzed by gas chromatography technique associated with the mass spectrometry GC/MS. The results of the analysis showed that the essential oil of Qadmus area contained 26 components,which accounted for (99.98%) of total essential oil. The main component was : exo 6-carbonyl methoxy tricycle [2.2.1.0(2,7)] heptane, by 21.89%. The results of the analysis showed that the essential oil of Einaza area contained 55 components, which accounted for (99.96%) of total essential oil. The main component was : Trispiro(2.1.2.1.2.1)dodecane -4,8,12-trione, by 11.38%. Keywords: Hypericum Perforatum.L,St. John’s wort, Hypericaceae family, hydrodistillation ,GC-MS.